2015
DOI: 10.22338/mka.v37.i1.p1-7.2014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acinetobacter Baumannii Isolated From Clinical Specimens in Adam Malik Hospital

Abstract: AbstrakAcinetobacter baumannii merupakan spesies Acinetobacter spp. tersering diisolasi dari manusia, dan lebih sering dijumpai pada infeksi nosokomial dibandingkan dengan infeksi di komunitas. Eksistensi bakteri ini di lingkungan terkait dengan keragaman reservoir, kemampuan memperoleh gen pembawa sifat resisten antimikroba, dan sifat resisten terhadap pengeringan. Infeksi disebabkan strain A.baumannii yang resisten terhadap banyak antibiotik tidak mudah dikendalikan dan menjadi permasalahan di berbagai negar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
7
0
5
Order By: Relevance
“…Acinetobacter baumanii has remained an issue of great concern. This is attributed to different factors including the enormous ability of Acinetobacter baumanii to spread from along with colonization of human and environmental reservoirs [24] Detection of this organism in the samples used here is in conformity with Mayasari & Siregar [8]. Detection in these samples indicates colonization of some body systems and tracts such as the skin and urinary tracts.…”
Section: Nosocomial Acquisition Of Multi-drug Resistantsupporting
confidence: 62%
See 1 more Smart Citation
“…Acinetobacter baumanii has remained an issue of great concern. This is attributed to different factors including the enormous ability of Acinetobacter baumanii to spread from along with colonization of human and environmental reservoirs [24] Detection of this organism in the samples used here is in conformity with Mayasari & Siregar [8]. Detection in these samples indicates colonization of some body systems and tracts such as the skin and urinary tracts.…”
Section: Nosocomial Acquisition Of Multi-drug Resistantsupporting
confidence: 62%
“…"Acinetobacter baumannii has become increasingly responsible for causing hospital acquired infections (HAI), particularly in intensive care units (ICUs)" [7]. "It has been isolated from blood, sputum, skin, pleural fluid, and urine, usually in device associated infections" [8]. "The species are excellent biofilm producing bacteria, which facilitate their survival in hospital environments and are frequently found on the skin and in the respiratory and urinary tracts of hospitalized patients" [9].…”
Section: Introductionmentioning
confidence: 99%
“…Acinetobacter baumannii has become increasingly responsible for causing hospital acquired infections (HAI), particularly in intensive care units (ICUs) [ 4 ]. It has been isolated from blood, sputum, skin, pleural fluid, and urine, usually in device associated infections [ 5 ]. The species are excellent biofilm producing bacteria, which facilitate their survival in hospital environments and are frequently found on the skin and in the respiratory and urinary tracts of hospitalized patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…No wonder the strain of Acinetobacter resistant to carbapenem is rapidly found around the world, creating a challenge in treatment. 9 Research conducted by Mayasari 10 and Siregar 10 as well as by Kardana 11 showed that the resistance level of A.baumannii to meropenem was quite high.…”
Section: Introductionmentioning
confidence: 99%